The Potential of Information and Communication Technology to Promote Sustainable Natural Resources Management and Its Unintended Consequences - Tom, Teckshawer (Technium Social Sciences Journal, 2023)
A formidable tool with the potential to improve conservation and sustainable management of natural resources is information and communication technology (ICT). It is possible to address the problems of resource depletion and biodiversity loss by using ICT in many elements of environmental conservation, such as monitoring, data collection, and public awareness. However, it's crucial to consider the unexpected repercussions that could result from the broad use of ICT in this setting.In order to promote sustainable natural resource management and conservation, this study will examine any unintended implications of ICT. The study also identifies and examines four important areas of concern, including digital divide, data privacy and security, e-waste management, and ecological footprint, based on pertinent research and case examples. The research seeks to educate policymakers, practitioners, and academics about the importance of using ICT in environmentally conscious ways by emphasizing these unintended consequences particularly in African countries.